2019
DOI: 10.12944/crnfsj.7.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Heavy Metal Profile of Nigerian Rice Varieties

Abstract: This study was carried to assess the nutritional composition and heavy metal profile of Nigerian rice varieties. A total of one hundred samples consisting of twenty five samples each of four varieties of white unpolished Nigerian local rice Oryzaglaberrima (Ofada rice, Abakaliki rice, Ekpoma rice and Igbimo rice) were purchased from Ofada in Ogun State, Nigeria. Flour samples produced from the rice varieties were evaluated for nutritional (proximate, amino acids and vitamins profile analyses) qualities and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
2
2
1
Order By: Relevance
“…The TDF content of grains in this study was found to be as follows: red and white sorghum > white corn > red and white millet > ofada rice > red and white fonio. Our results are generally consistent with the available literature, which reports values of 3.3–8% in hulled fonio, 3.7–15% in pearl millet, 8.6–21.0% in sorghum, 1.4–3.5% in ofada rice, 11.1–15.34% and 2.1–10.1% in corn [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 20 , 21 , 22 ]…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The TDF content of grains in this study was found to be as follows: red and white sorghum > white corn > red and white millet > ofada rice > red and white fonio. Our results are generally consistent with the available literature, which reports values of 3.3–8% in hulled fonio, 3.7–15% in pearl millet, 8.6–21.0% in sorghum, 1.4–3.5% in ofada rice, 11.1–15.34% and 2.1–10.1% in corn [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 20 , 21 , 22 ]…”
Section: Discussionsupporting
confidence: 93%
“…The TDF content of grains in this study was found to be as follows: red and white sorghum > white corn > red and white millet > ofada rice > red and white fonio. Our results are generally consistent with the available literature, which reports values of 3.3-8% in hulled fonio, 3.7-15% in pearl millet, 8.6-21.0% in sorghum, 1.4-3.5% in ofada rice, 11.1-15.34% and 2.1-10.1% in corn [3][4][5][6][7][8][9][10][11][12][20][21][22] The total PA content of the grains selected for analysis in this study ranged from 276.64 to 2202.5 ng/mg, as the total PA amount in wholegrains can differ subject to the grain type, the environment and farming methods, as well as the different types of processing applied, the PAs selected for characterisation, as well as the extraction procedures and analytical methods applied. One study showed that total PAs differed significantly based on the type of corn [23] and rice cultivars [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The carbohydrate content of the rice variety in Harir sub-district is low ranging from 25.8 at 3 months to 48.5 at 5 months. This is not in agreement with the work of Adeyeye et al [34] who reported high content of carbohydrates in the studied rice varieties. Vitamin P or rutoside are other names for rutin.…”
Section: Proximate Analysis In Rice Samplescontrasting
confidence: 99%
“…Vitamin P or rutoside are other names for rutin. Its structure includes the disaccharide rutinose and the flavonolic aglycone quercetin glycoside [34]. According to Ganeshpurkar and Saluja [35], rutin exhibits a variety of pharmacological properties including anti-oxidant, cytoprotective, vaso-protective, anti-carcinogen, neuroprotective, cardio-protective, and anti-hyperglycemic and anti-oxidant activity in streptozotocin-induced diabetic rats [36].…”
Section: Proximate Analysis In Rice Samplesmentioning
confidence: 99%